THE SIGNIFICANCE OF SOCIAL DEVELOPMENT IN EDUCATIONAL PROCESSES - Master Nurmatov E. O. (Modern American Journals, 2025)
The content of this article contains thoughts and opinions about the importance of social maturity in the educational process. Thoughts are given about the characteristics of the development of social maturity in the educational process.
Keywords: Social maturity, education, students, educational process, pedagogy.